Database Systems - Peter Rob (Cengage Learning, Inc, 2004)
Database Systems: Design, Implementation, and Management, Sixth Edition takes you clearly and effectively through the entire process of database development and implementation. This market leading text is the most comprehensive and detailed coverage of database basics and is complemented with ample exercises and problems at the end of each chapter to encourage hands-on learning, plus a two-chapter step-by-step running case. This new, sixth edition includes new Visio and UML tutorials, as well as a new chapter on Advanced SQL. All appendices are housed on a CD that accompanies every copy of the text